Ecology of Vespidae (Hymenoptera)Predators in Coffea arabica Plantations - Fernandes, Flavio Lemes (Sociobiology, 2014)
Social Vespidae exhibit control of Leucoptera coffeella (Lepidoptera: Lyonetiidae) in Brazil. The objective was to determine the ideal unit for sampling of predaceous Vespidae in coffee crops in the vegetative and reproductive phases. This research was conducted in two coffee plantations in Viçosa, MG. The factors being studied were: crop phase, canopy thirds, branch type, exhibition side of the plant to solar light and the position of the leaf on the branch. The number of predation mines by Vespidae on all the leaves of each evaluated plant was recorded. In coffee plants in the vegetative phase the best sampling unit of the Vespidae was the 5th or 6th pair of leaves on the primary plagiotropic branches of the median third of the canopy. In coffee plants already in the reproductive phase the best unit for sampling Vespidae were leaves on the third apical of the 4th or 6th pair of leaves on primary plagiotropic branches on the plant face exposed to the sun in the afternoon period or on the median third on the 5th pair of leaves of the plant face exposed to the sun in the afternoon period.